Cerebellar ataxias: an update. Issue 1 (February 2020) - Manto, Mario; Gandini, Jordi; Feil, Katharina; Strupp, Michael
Abstract : Purpose of review: Providing an update on the pathophysiology, cause, diagnosis and treatment of cerebellar ataxias. This is a group of sporadic or inherited disorders with heterogeneous clinical presentation and notorious impact on activities of daily life in many cases. Patients may exhibit a pure cerebellar phenotype or various combinations of cerebellar deficits and extracerebellar deficits affecting the central/peripheral nervous system. Relevant animal models have paved the way for rationale therapies of numerous disorders affecting the cerebellum. Recent findings: Clinically, the cerebellar syndrome is now divided into a cerebellar motor syndrome, vestibulocerebellar syndrome and cerebellar cognitive affective syndrome with a novel clinical scale. This subdivision on three cornerstones is supported by anatomical findings and neuroimaging. It is now established that the basal ganglia and cerebellum, two major subcortical nodes, are linked by disynaptic pathways ensuring bidirectional communication. Inherited ataxias include autosomal recessive cerebellar ataxias (ARCAs), autosomal dominant spinocerebellar ataxias and episodic ataxias and X-linked ataxias. In addition to the Movement Disorders Society genetic classification of ARCAs, the classification of ARCAs by the Society for Research on the Cerebellum and Ataxias represents major progress for this complex subgroup of cerebellar ataxias. The advent of next-generation sequencing has broadened the spectrum of cerebellar ataxias. Summary: Cerebellar ataxias require a multidisciplinary approach for diagnosis and management. The demonstration of anatomical relationships between the cerebellum and basal ganglia impacts on the understanding of the cerebello-basal ganglia-thalamo-cortical system. Novel therapies targeting deleterious pathways, such as therapies acting on RNA, are under development.